Groupthink Dalam Komunitas One Piece Bengkulu Rafflesia(Studi Deskriptif Kualitatif Di Community One Piece Bengkulu Rafflesia) - Rizady Alvitara; Yanto Yanto; Bayu Risdiyanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The problem raised in this study is what are the symptoms of groupthink that occur in the Community One Piece Bengkulu Rafflesia which has several advantages compared to other communities, one of which is that this community adheres to a family system within it. The method used in this study was a qualitative descriptive method by producing descriptive data in the form of written or spoken words from the people being observed. Data collection techniques used were interviews, observation, documentation and literature study. This study used the theory of groupthink from Irvin. L. Janis as the main theorist. The results of the study show that the symptoms of groupthink that arise in this community are the perception of invincibility, belief in group morality, collective rationality, illusions about unanimity and pressure on those who disagree. The symptoms of groupthink arise because the group members already feel very confident that their group is the best group compared to other groups. Even so, not all the conditions and symptoms described in theory occur. because basically, all members of the group still maintain each other's integrity.